Preoperative Inflammatory Control and Surgical Outcome of Vitrectomy in Intermediate Uveitis - Yong Un Shin; Joo Young Shin; Dae Joong Ma; Heeyoon Cho; Hyeong Gon Yu (Journal of Ophthalmology)
Purpose. To demonstrate the long-term effectiveness of vitrectomy for intermediate uveitis (IU) and to determine whether complete control of inflammation before vitrectomy is necessary. Methods. This retrospective study included 66 eyes of 66 patients with IU who underwent vitrectomy for vitreoretinal complications. Eyes were followed for at least 12 months after vitrectomy. The degree of inflammation control and visual acuity were compared before and after vitrectomy. These parameters were compared according to the presence of complete inflammation control before surgery. Results. The indications of vitrectomy included epiretinal membrane (26 eyes), vitreous opacity (21 eyes), and tractional retinal detachment (12 eyes), among others. Uveitic attacks did not occur in 44 of the 66 patients after vitrectomy. The numbers of uveitis attacks, local steroid injections, and systemic medications significantly decreased, and vision meaningfully improved after vitrectomy. These parameters did not differ significantly, regardless of the presence of preoperative inflammation. Conclusions. This study showed that vitrectomy is a good modality to manage vitreoretinal complications associated with IU, even if complete control of intraocular inflammation is not achieved before vitrectomy.